N-(4-Methylphenyl)-6-(pyrazol-1-yl)pyridazin-3-amine - Ather, Abdul Qayyum (International Union of Crystallography, 2010)
In the title compound, C(14)H(13)N(5), the pyrazole ring is disordered over two orientations in a 0.571 (10):0.429 (10) ratio and the dihedral angle between the pyridazine ring and the benzene ring is 28.07 (10)°. In the crystal, pairs of N—H⋯N and C—H⋯N hydrogen bonds link the molecules into dimers, with the aid of a crystallographic twofold axis. The packing is consolidated by further C—H⋯N bonds and weak C—H⋯π interactions.